Electrochemical Behaviors of Resveratrol and Its Interaction with DNA. Issue 10 (26th June 2014) - Gao, Lin; Wei, Xiaohan; Wang, Fei; Zhang, Bingying
Abstract: Electrochemical behavior of resveratrol was studied in Britton‐Robinson (B‐R) buffer solution (pH = 4.0) at glassy carbon electrode (GCE) using cyclic voltammetry (CV). Resveratrol showed an irreversible anodic peak at 0.570 V which was involving one electron and one proton. Also, the interaction of resveratrol with double‐stranded fish sperm DNA was investigated by linear sweep voltammetry (LSV) and UV‐vis spectra. The results showed that peak potentials shifted to more positive value and peak currents decreased in electrochemical experiment and the maximum absorption decreased with red shift in UV‐vis spectra experiment with the addition of DNA, indicating the resveratrol interacted with DNA by intercalating into the double helix of DNA. Besides, the binding of resveratrol with DNA, analyzed in terms of the cooperative Hill model, yields the association constant K a = 3.18 × 10 5 and a Hill coefficient m = 1.06. Abstract : The interaction of resveratrol with DNA has been investigated using cyclic voltammetry, linear sweep voltammetry and UV‐visible spectroscopy. The results showed that the resveratrol interacted with DNA by intercalating into the double helix of DNA.